Omega-3 Index, fish consumption, use of fish oil supplements and first clinical diagnosis of central nervous system demyelination - Daly, Alison; Martin, Christopher; Sherriff, Jill; Mori, T.A.; Pereira, Gavin; Lucas, R.M.; Ponsonby, A.L.; Taylor, B.; van der Mei, I.; Black, Lucinda; Ausimmune Investigator Group (ELSEVIER SCI LTD, 2021)
Higher intakes of omega-3 polyunsaturated fatty acids (n3PUFAs) have been associated with lower MS risk. We aimed to test associations between the Omega-3 Index, blood levels of n3PUFAs, fish oil supplement use, and fish consumption with a first clinical diagnosis of CNS demyelination (FCD). Cases (n = 250) had a higher Omega-3 Index compared with a matched group of controls (n = 471) (average treatment effect (ATE)=0.31, p = 0.047, based on augmented inverse probability weighting). A higher percentage of cases than controls used fish oil supplements (cases=17% vs. controls=10%). We found that Omega-3 Index increased as time between FCD and study interview increased (e.g., at or below median (112 days), based on ATE, mean=5.30, 95% CI 5.08, 5.53; above median, mean=5.90, 95% CI 5.51, 6.30). Fish oil supplement use increased in a similar manner (at or below median (112 days), based on ATE, proportion=0.12, 95% CI 0.06, 0.18; above the median, proportion=0.21, 95% CI 0.14, 0.28). Our results suggest a behaviour change post FCD with increased use of fish oil supplements.